MASYARAKAT KORUP DAN PENYEBABNYA PADA NOVEL KORUPSI KARYA PRAMOEDYA ANANTA TOER - Allien, Astri Adriani (HUMANIKA, 2012)
This paper aims to discuss the condition of corrupt society in the early era after the Indonesian independence as depicted in the novel Korupsi written by Pramoedya Ananta Toer. One’s acts are closely related to the place or the invironment where she/he lives. This statement is relevant with triadic concept of race, milieu and moment as stated by Hippolyte Taine. By using the sociological approach of literature, the study shows that corruption committed by the main character of Korupsi caused by poverty and the opportunity possessed by a public servant. With this stereotype, we can make the novel as a document in expressive research. Keywords: corruption, race, milieu, moment, stereotype